BETWEEN SIMPLICITY AND TECHNICAL DIFFICULTIES: PERCEPTIONS OF TECHNOLOGIES FOR MONITORING PUBLIC CONTRACT MANAGEMENT - Souza, Carla Sabrina dos Santos; Barbosa, Reinaldo Azevedo; Fully, Roberto Miranda Pimentel (Seven Editora, 2026)
The study analyzed the perceptions of assistants and monitors regarding the usability of digital technologies applied to the monitoring of public contract management within the Ministry of Development and Social Assistance, Family and Fight Against Hunger (MDS) and the Department of Support and Shelter Entities Working with Alcohol and Drugs (DEPAD). The research employed statistical textual analysis using the IRaMuTeQ software, processing a corpus composed of 46 respondents and 148 context units, totaling 5,000 lexical occurrences. The results confirmed that the simplicity and clarity of KoboToolbox fostered positive usability perceptions, whereas technical failures of uMov.me generated dissatisfaction and compromised effectiveness. Furthermore, the analysis revealed differences between profiles: assistants prioritized subjective evaluations, while monitors emphasized technical and institutional aspects, validating the four proposed hypotheses. It is concluded that technological adoption in public contract monitoring depends on the interaction between design factors, technical performance, and functional profile, requiring differentiated training and investments in platform stability.